2004
DOI: 10.1177/000348940411300806
|View full text |Cite
|
Sign up to set email alerts
|

Fdg-Pet Scan in Local Follow-up of Irradiated Head and Neck Squamous Cell Carcinomas

Abstract: We performed a prospective study to assess the value of positron emission tomography (PET) with 2-[18F]-fluoro-2-deoxy-D-glucose (FDG) in the prediction of local control in irradiated head and neck squamous cell carcinomas (HNSCCs). Forty-two patients with irradiated HNSCCs underwent 49 FDG-PET scans between 3 and 6 months after the end of radiotherapy. The mean follow-up time after the first FDG-PET scan was 17 months. The result of the FDG-PET scan was true-positive in 6 patients, false-positive in 7 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 23 publications
0
15
0
3
Order By: Relevance
“…PET is able to detect residual nodal disease in patients with a partial response to CR with a reported sensitivity of 71% to 100%, specificity of 43% to 100%, positive predictive value of 46% to 100%, and negative predictive value of 66% to 100% 23,24,26–30 . The efficacy of PET in detecting residual or recurrent disease depends on the timing of PET imaging after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…PET is able to detect residual nodal disease in patients with a partial response to CR with a reported sensitivity of 71% to 100%, specificity of 43% to 100%, positive predictive value of 46% to 100%, and negative predictive value of 66% to 100% 23,24,26–30 . The efficacy of PET in detecting residual or recurrent disease depends on the timing of PET imaging after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The 2‐[fluorine‐18]fluoro‐2‐deoxy‐d‐glucose (FDG) positron emission tomography (PET), in combination with CT (PET‐CT), is increasingly being used in the management of patients with head and neck cancer, including initial staging, assessing response to therapy, detecting recurrence, and identifying unknown primary tumors . Additionally, PET‐CT is increasingly used to improve the accuracy of staging in recurrent laryngeal cancer .…”
Section: Introductionmentioning
confidence: 99%
“…The timing after radiotherapy (RT) is also important, scans which are positive after 4 weeks indicate residual disease, but a negative scan is unreliable with a NPV of 14% [27], however a scan at 4 months may more accurately reflect disease with a negative predictive value of 100%, suggesting that no biopsy will be needed for at least one year if the PET is negative [28]. Greven et al [29] found FDG-PET useful for the initial imaging of head and neck cancer but the initial SUV did not predict response to RT, and the 1 month post-RT scan was inaccurate (35% false negative) with the 4-month post-RT scan a better predictor for the presence of residual tumour.…”
Section: Response To Therapymentioning
confidence: 99%